It's Justin Time, Amber Brown - Danziger, Paula, 1944-2004 (Danziger, Paula, 1944-2004. A is for Amber., 2001)
Unlike her best friend Justin, Amber Brown loves to measure time and hopes to receive a watch on her seventh birthday.